Moral Value for Young People in Using The Internet - Maksud Hakim (Institute of Computer Science (IOCS), 2022)
The internet makes it easy for all people, especially young people, to communicate. With the advancement of internet and cell phone technology, social media is also growing rapidly. Young people in the modern era are proficient in managing and using computer technology in using the Internet. This study uses a qualitative approach with literature study methods related to Moral Values, Youth and the Internet. The results of the study explain that the modern era can be said to be an era where there is a lot of development, be it cultural developments, educational developments and technology. So it is a pity if the use of the internet actually makes the younger generation have no moral values in themselves. Therefore, so that young people always use moral values in using the internet, there are several things that can be considered and applied, namely, instilling religious values, increasing awareness of young people, and the role of increasing discipline.